Yemen : A Natural Gas Incentive Framework - World Bank (Washington, DC, 2012)
Yemen is planning to export gas through Yemen Liquefied Natural Gas (YLNG) starting from 2009. Yemen is also aiming to develop the domestic gas market, in particular gas-to-power. Liquefied Natural Gas (LNG) export revenue and domestic gas sales are expected to partially offset the decline in crude oil revenue from currently producing fields. The development of a gas sector has the potential to substantially contribute to Yemen's economic growth and fiscal revenue generation. Because of the high risk and considerable investment involved in developing a gas sector, attracting foreign capital and expertise will be essential. To this end, in addressing the public interest and developing the preferred policies, Yemen should ensure that decisions on project development and technologies will be based on their economic merits, and gas will be allowed to find its highest value market.